New synonym, new combination and typifications in Varronia (Cordiaceae, Boraginales) - Silva, Thaynara De Sousa; Melo, José Iranildo Miranda De (Phytotaxa, 2019)
Due to their recent reestablishment at the generic level, some species of the genus Varronia need to be (re-)allocated and their names and respective nomenclature types reviewed. One new combination (V. serratifolia) and a new synonym (V. intonsa) are proposed here. To promote nomenclatural stability, the historical of the names of widely distribute species is discussed and a lectotype is assigned to V. globosa, a lectotype and an epitype for V. curassavica. The names V. hermanniifolia, C. hermanniifolia var. calycina, Cordia sessilifolia var. macrantha, and V. villicaulis are also lectotypified. A neotype is designated to V. paucidentata.